Comparative Analysis between Notations to Classify Named Entities using Conditional Random Fields - Amaral, Daniela Oliviera F. do; Buffet, Maiki; Vieira, Renata (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2015: Anais do X Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2015)
Conditional Random Fields (CRF) is a probabilistic Machine Learning (ML) method based on structured prediction. It has been applied in several areas, such as Natural Language Processing (NLP), image processing, computer vision, and bioinformatics. In this paper we analyse two different notations for identifying the words that compose a Named Entity (NE): BILOU and IO. We found out that IO notation presents better results in F-measure than BILOU notation in all categories of HAREM corpus.